Defining critical aspects in interaction: examples from a learning study on welding based on CAVTA. Issue 5 (7th April 2022) - Kilbrink, Nina; Axelsson, Jan; Asplund, Stig-Börje
Abstract : Purpose: The purpose of this study is to explore how critical aspects can be defined in a learning study on welding without conducting any pre-tests. Design/methodology/approach: In this study, the authors focus on empirical examples from a learning study on welding conducted in six iterative cycles, with conversation analysis and variation theory approach (CAVTA) as a theoretical basis. The welding lessons have been video-recorded, and in the study, the authors analyze examples where the teachers try to identify critical aspects of a vocational practical object of learning in interaction. CAVTA permeates the complete process, where the analysis has been part of the iterative cycles and further developed when the six cycles were completed. Findings: The results show how critical aspects can be made visible in the interaction between teacher(s) and student(s) in the enacted learning situation. In the process, the authors work with the three concepts expected critical aspects, displayed critical aspects and targeted critical features in relation to a vocational practical object of learning where conducting a pre-test to define critical aspects is not educationally possible. Originality/value: Teaching vocational practical objects of learning could be seen as something different from teaching other kinds of objects of learning and the use of the traditional pre-tests in learning studies may be problematic. From that follows, that other ways of finding the critical aspects for the students regarding a vocational practical object of learning might be needed. In this study, such a way is presented.